2018
DOI: 10.1029/2018jb016117
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Density Structure, Lithosphere Flexure Mechanism, and Isostatic State Throughout the Qinling Orogen Revealed by In Situ Dense Gravity Observations

Abstract: Gravity and GPS hybrid measurements were conducted at 385 stations throughout the Qinling Orogen, China, to update Bouguer gravity anomalies and free‐air gravity anomalies of the area. The crustal density structure, lithosphere flexure mechanism, and isostatic state of the Qinglin Orogen were studied in detail via these in situ observations. Bouguer gravity anomalies in the study area are mainly negative, ranging from −410 mGal in the Tibetan Plateau to −100 mGal in the eastern Qinglin Orogen. The estimated cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…A comparison with higher-resolution density models in different parts of the world (e.g. Kozlovskaya et al 2004;Yegorova et al 2013;Hasterok & Gard 2016;Gradmann et al 2017;Sippel et al 2017;Alghamdi et al 2018;Wang et al 2018) shows a close agreement with our crustal density values.…”
Section: Crustal and Mantle Densitiessupporting
confidence: 85%
“…A comparison with higher-resolution density models in different parts of the world (e.g. Kozlovskaya et al 2004;Yegorova et al 2013;Hasterok & Gard 2016;Gradmann et al 2017;Sippel et al 2017;Alghamdi et al 2018;Wang et al 2018) shows a close agreement with our crustal density values.…”
Section: Crustal and Mantle Densitiessupporting
confidence: 85%
“…The observation and data procedure methods follow our previous studies (Fu et al, 2014; Fu & She, 2017; Wang et al, 2018). Two Burris gravimeters (B105 and B115) were used to carry out the data on gravity.…”
Section: Gravity Observations At the Ehsmentioning
confidence: 99%
“…Hu and Yao (2018) compared their Vs velocity results with the resistive structure from the magnetotelluric data (Lin et al, 2017) and found that the tomography and magnetotelluric results are totally the same. The conversion relationship between density and Vs is from Wang et al (2018). The initial Moho depths are based on the results of receiver function (Wang et al, 2019).…”
Section: Density Structures Of the Ehsmentioning
confidence: 99%
“…To the south of the study area is the Qinling Orogen, whose eastern and western parts have been uplifted by subduction of the North and South China Blocks and lower crustal flow from the Tibetan Plateau, respectively. The Qinling Orogen is relatively complex because it is situated at the conjunction zone of three main tectonic blocks (Wang et al 2018).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Gravity and GPS data used in this study were obtained from in situ observations conducted in 2014 and 2017 (Wang et al 2018). Normal correction, free-air correction, Bouguer correction, and terrain correction were performed on the adjusted gravity data to obtain complete BGA (Fig.…”
Section: Data Processingmentioning
confidence: 99%